Pengaruh Akuntabilitas, Partisipasi Masyarakat Dan Transparansi Terhadap Efektivitas Pengelolaan Dana Desa : (Studi Kasus Kecamatan Seruway Kabupaten Aceh Tamiang) - Nurul Arifin; Afrah Junita; Nasrul Kahfi (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This research aims to determine the influence of accountability, community participation and transparency regarding the effectiveness of fund management village. This research is quantitative research using types Primary data obtained from questionnaires and measured using a scale likert. The population in this study used all villages in Seruway District has 24 villages. Sampling technique using stratified random sampling. Sample criteria in this study is the Village Head/Village Secretary, MDSK and 2 Village People in every village in the entire Seruway Aceh Tamiang District for a total a total of 96 respondents. Data analysis techniques in this research using multiple linear regression analysis with the help of SPSS version 25. The results of this research indicate that the Accountability variable (X1) is not significant effect on the effectiveness of village fund management, variable Community Participation (X2) has a positive and significant effect on The effectiveness of village fund management, as well as the Transparency variable (X3) have an influence positively and significantly on the effectiveness of village fund management.